Modern libraries practices for teaching information literacy - N. S. Redkina (Библиосфера, 2019)
Information literacy as a set of techniques and methods to work with diverse types of information is a necessary condition for s person to exist in the modern world, because it helps to develop personal, professional and educational skills. The concept of information literacy firstly appeared in the United States in the 1970th. It was a response to the development of information society. Up to now the idea has not lost its relevance, due to the intensive growth of information technologies, an increase in information volumes and the emergence of new educational paradigms. Since the 1990th libraries began to actively develop programs and implement methods of increasing information literacy, systematically train users in rational methods of search, analytical and synthetic information processing, extraction, evaluation and transformation, as well as in the grounds of information security. The purpose of this article is to identify current advanced practices of libraries on various training forms to develop users’ information literacy, taking into account the increase in information flows and the emergence of large amounts of misinformation, the expansion of information types, the capabilities of education technologies, including online, library directions of work activities. To get information use was made of the Scopus database (the selection criterion: journal publications from 2015 to 2019 on the topic “information literacy”). The publication analysis has shown that libraries choose various ways and methods to teach information literacy their users: embedding programs in the educational process (academic libraries); through game, interactive forms (public libraries), individual methods of work of subject librarians with readers, as well as online instructions that allow formation of skills for effective search and information processing in any format.